Sexual Orientation and Sexual and Reproductive Health among African American Sexual Minority Women in the U.S. South. - Agénor, Madina.; Austin, S. Bryn.; Kort, Daniel.; Austin, Erika L.; Muzny, Christina A. (Tufts University. Tisch Library., 2019)
Research on the sexual and reproductive health of sexual minority women, especially those of color, is limited. Using multivariable Poisson regression, we estimated risk ratios for the association between two dimensions of sexual orientation (sexual identity and sexual behavior) and five sexual and reproductive health indicators (pregnancy, contraceptive use, human immunodeficiency virus [HIV] testing, Pap test use, and sexual assault) among African American sexual minority women in the U.S. South (n = 165)